Long-term stability studies on protection against Newcastle disease by commercial live vaccine used in Brazil - Orsi, Maria Angela; Zaroni, Margarida Maria H.; Doretto Junior, Luciano; Albieri Camillo, Soraya Cecilia; Mendes Ribeiro, Simone Alves; Spilki, Fernando Rosado; Buzinaro, Maria da Gloria [UNESP]; Arns, Clarice Weis (Academic Press Ltd Elsevier B.V. Ltd, 2009)
The thermostability (TS) and efficacy offered by live vaccines against Newcastle disease strains B 1, La Sota, VG-GA and Ulster, produced or imported by four Brazilian laboratories, were evaluated during their validity period. Kinetic profiles were obtained from samples conserved in refrigerators during 0, 4, 8, 12, 16, 20 and 24 months after their manufacturing. The statistical analysis of the vaccine titre effect obtained by the fresh air (FA) method showed that the vaccine profiles were parallel and coincident, presenting a significant descending trend. The vaccine titres and efficiency proofs at the end of the validity period were above the level of legislation requirements and showed an average loss in titre of 0.40 and 0.66 log(10), within the first and second validity years, respectively. The titre obtained by TS, within the month after manufacturing, had no significant difference from the titre obtained by FA within 24 months after manufacturing, being their pairs of observations positively correlated (r = 0,49, p = 0.0003), showing that the TS method, which anticipates the vaccines' performance at the end of the validity period, can substitute the FA method 24 months after manufacturing. (C) 2009 The International Association for Biologicals. Published by Elsevier Ltd. All rights reserved.
Keywords: Thermostability; Protection; Newcastle disease vaccines; Commercial live vaccines; Virus vaccine